Etyka administracji publicznej a funkcja edukacyjna sądów administracyjnych – glosa częściowo krytyczna do wyroku Naczelnego Sądu Administracyjnego z 15 lipca 2021 r., sygn. akt III OSK 3869/21 - Jaworski, Arkadiusz (Studia Prawa Publicznego, 2024)
This gloss discusses two, at first glance imperceptible, problems that are concentrated in the ruling analyzed. The first of these is the practical application of ethical principles by public administration bodies. In the case being commented on – submitting an application for a school scholarship beyond the statutory deadline – the public administration authorities not only failed to fulfill their obligations related to the fair consideration of the case, but also to provide protection to a family in a difficult life situation. Such protection is guaranteed not only by statutes, including the Code of Administrative Procedure, but also by the Constitution of the Republic of Poland and international agreements binding on Poland. The Supreme Administrative Court’s judgment focused primarily on the analysis of the provisions of the Education System Act, without paying much attention to the above-mentioned problem of standards that should guide public administration. In the author’s opinion, such a way of considering the case, which ignores the broader context of the primary causes of the entire problem, should be considered as a serious omission. In the light of the fundamental role of the courts in protecting the fundamental rights of the individual, as well as the influence of case law on shaping the legal culture of public authorities and society, the duty of the court – especially the court of last instance – is to provide a detailed explanation of all doubts that have arisen in a given case and a comprehensive justification of the reasons for a given decision. The goal that the court should strive for is not only to uphold and promote certain standards or maintain the uniformity of case law, but also to ensure that both the parties and all other recipients of the judgment have no or the least possible doubts as to the correctness of the judgment. All this significantly affects the authority of the judiciary and the trust of citizens in it, and thus to some extent, also their faith in the entire public authority in Poland.